Tathwir Ansyithah al-Ta’allum al-Mustaqillah li Tanmiyah Maharah al-Kalam fi Madrasah Tsanawiyah al-Hukumiyah Indonesia - Thoriq, Muhammad Ahsan; Nurhidayati, Nurhidayati; Ahsanuddin, Mohammad (Institut Agama Islam Negeri Curup, 2023)
This research aimed to produce technology-based independent learning materials to enhance students' speaking skills. The researchers employed the ADDIE development methodology to create self-learning materials. The researchers concluded that there was a difference in students' speaking skills before and after using self-learning materials, including speeches, debates, news reading, and poetry. Respondents in this study were required to answer questions posed by the researchers both before and after using the learning materials. The participants in this research were 21 students in the eleventh grade at a government high school in Indonesia. Data analysis utilized descriptive quantitative percentages and t-tests to assess the impact and effectiveness of the learning materials with the assistance of IBM SPSS Statistics 25. The students showed interest in the technology-based independent learning materials provided, and they were able to understand the content of the presented videos. Using self-learning materials has been proven beneficial for students in developing their speaking skills. Technology-based self-learning materials can be implemented in the educational process across various fields. Visual materials, such as videos, facilitate students’ faster understanding.